2008
DOI: 10.1093/humrep/den295
|View full text |Cite
|
Sign up to set email alerts
|

Germ cell differentiation in the marmoset (Callithrix jacchus) during fetal and neonatal life closely parallels that in the human

Abstract: BACKGROUNDTesticular germ cell tumours (TGCT) are thought to originate from fetal germ cells that fail to differentiate normally, but no animal model for these events has been described. We evaluated the marmoset (Callithrix jacchus) as a model by comparing perinatal germ cell differentiation with that in humans.METHODSImmunohistochemical profiling was used to investigate germ cell differentiation (OCT4, NANOG, AP-2γ, MAGE-A4, VASA, NANOS-1) and proliferation (Ki67) in fetal and neonatal marmoset testes in com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
134
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(148 citation statements)
references
References 36 publications
12
134
1
1
Order By: Relevance
“…Moreover, it is interesting to note that the late gestation period of low proliferation in human fetal gonocytes partially overlaps with the phase of highest DNA methyl transferase expression (GW21-GW29), strikingly reminiscent of the high DNA methylation activities observed during late gestation in rodent gonocytes (Galetzka et al 2007). In marmoset, in which gestation lasts 22 weeks, similar fluctuations in proliferation rates were observed, with maximal proliferation at GW11-GW14, a decrease at GW15-GW16, followed by an increase to 40% of proliferating gonocytes at GW17-GW20, and a return to a lower rate until 6 weeks after birth (Mitchell et al 2008). A subsequent study by the same group concurred with a proliferation index of 29% in GW12-GW17 fetal gonocytes, decreasing to values of w10% in infants from the first postnatal week to 5 months (McKinnell et al 2013).…”
Section: Insights From Non-rodent Speciesmentioning
confidence: 59%
See 2 more Smart Citations
“…Moreover, it is interesting to note that the late gestation period of low proliferation in human fetal gonocytes partially overlaps with the phase of highest DNA methyl transferase expression (GW21-GW29), strikingly reminiscent of the high DNA methylation activities observed during late gestation in rodent gonocytes (Galetzka et al 2007). In marmoset, in which gestation lasts 22 weeks, similar fluctuations in proliferation rates were observed, with maximal proliferation at GW11-GW14, a decrease at GW15-GW16, followed by an increase to 40% of proliferating gonocytes at GW17-GW20, and a return to a lower rate until 6 weeks after birth (Mitchell et al 2008). A subsequent study by the same group concurred with a proliferation index of 29% in GW12-GW17 fetal gonocytes, decreasing to values of w10% in infants from the first postnatal week to 5 months (McKinnell et al 2013).…”
Section: Insights From Non-rodent Speciesmentioning
confidence: 59%
“…Several studies have used primate models as surrogate for humans. Among them, studies in marmosets (Callithrix jacchus) have shown that germ cell differentiation occurs in a manner similar to that observed in humans, when analyzed at the level of common gene expression and cellular processes (Mitchell et al 2008). At the molecular level, Mitchell et al have shown that marmoset gonocyte differentiation results in decreased expression of the pluripotency markers OCT4 and NANOG and increase in VASA (DDX4) gene expression.…”
Section: Insights From Non-rodent Speciesmentioning
confidence: 93%
See 1 more Smart Citation
“…Women gave consent in accordance with United Kingdom national guidelines (70), and ethical approval was obtained from the local research ethics committee (71). Marmoset fetal testes (72) and mouse fetal testes (e18.5) (33) were obtained as described earlier.…”
Section: -Hsd3mentioning
confidence: 99%
“…SSCs and/ or spermatogonia). Similarly, decreasing NANOG expression is observed in differentiating gonocytes (Mitchell et al 2008), with detection of UCHL1 expression in SSCs during asymmetrical division of the cells (Luo et al 2009). Therefore, our results suggest the possibility that DBA-precoated plates may have resulted in transit characteristics of gonocytes towards SSCs and/or spermatogonia.…”
Section: Discussionmentioning
confidence: 92%